Prevalence of Popliteal Artery Variants in Free Tissue Transfer for Limb Salvage: A 12-Year Vasculoplastic Experience - Rohrich, Rachel N.; Li, Karen R.; Rutland, John W.; Lin, Ryan P.; Ferdousian, Sami; Attinger, Christopher E.; Youn, Richard C.; Akbari, Cameron M.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2025)
Popliteal artery variants (PAVs) are anatomical deviations of the popliteal artery's branching pattern and should be considered in microsurgical planning for patients undergoing lower extremity (LE) free tissue transfer (FTT). However, there is a significant lack of FTT literature in this patient population. Thus, this study presents our 12-year experience with LE FTT in patients with PAV.Patients receiving LE FTT reconstruction from July 2011 to March 2024 were reviewed. Preoperative angiograms were reviewed by a single vascular surgeon, and the presence of PAV was identified and classified as IIIA, IIIB, or IIIC. Primary outcomes were flap success and limb salvage.A total of 339 LE FTT were performed in 331 patients. A total of 32 patients (9.4%) had PAV, accounting for a total of 34 LE FTT. Class IIIA was the most common category (n = 20, 58.8%) followed by IIIB (n = 8, 23.5%) and IIIC (n = 6, 11.7%). Median age and body mass index were 63.5 (interquartile range [IQR]: 22.5) years and 27.4 (IQR: 10.3) kg/m2. The median Charlson Comorbidity Index was 5 (IQR: 2.5), with prevalent rates of diabetes (n = 18/32, 56.3%) and peripheral artery disease (n = 16/32, 50.0%). Median wound area was 71.0 (IQR: 80.0) cm2. Flap success rate was 100% (n = 34/34). At a median follow-up of 12.8 (IQR: 22.6) months, limb salvage was 97.1% (n = 33/34) and mortality was 6.3% (n = 2/32).In this large population of LE FTT, PAV occurs in almost 1 out of 10 patients. Essential to flap success and limb salvage is appropriate preoperative vascular imaging with arteriography, as the presence of PAV changes microsurgical intraoperative planning and technical considerations.
Keywords: limb salvage; popliteal artery variant; free tissue transfer; vasculoplastic approach; lower extremity reconstruction